APPLICATION OF TAXATION E-SYSTEM TO THE UNDERSTANDING OF ACCOUNTING STUDENT AT BINA BANGSA UNIVERSITY - Ina Khodijah; Raden Irna Afriani (EAJ (Economic and Accounting Journal), 2020)
Taxation e-system is a modernization of taxation using information technology. With the use of information technology in taxation, it is expected to be able to improve service to taxpayers, both in terms of quality and time so that it is more effective. But the knowledge of most taxpayers, especially students about the tax e-system is still low, so the Directorate General pf Taxes needs to socialize the existence of this tax e-system. The research objective is to determine the effect of the use of taxation e-system in the form of e-registration, e-spt, e-filling, e-billing to the understanding of accounting students. The research method used in this study is a quantitative descriptive approach. This research was conducted by distributing questionnaires to students who took the 2015 tax accountingconcentration at Bina Bangsa University, Banten. The results of this study indicate that partially e-registration and e-filling affect the understanding of accounting students. While e-spt and e-billing have no effect on the understanding of accounting students. But  simultaneously all e-registration, e-spt, e-filling and e-billing variables affect the understanding of accounting student.